Chronic hepatitis B infection presenting with chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS): a case report. (December 2015) - Weng, Ching-Fu; Chan, Ding-Cheng; Chen, Ya-Fang; Liu, Fei-Chih; Liou, Horng-Huei
Abstract Introduction Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids is a brainstem disorder characterized by perivascular pathologic reaction with lymphocyte infiltration and leading to diplopia, facial palsy, dysarthria, and gait ataxia. It was thought to be an autoimmune disorder without distinct pathogenesis. Chronic hepatitis B virus infection has been proposed in correlation with autoimmune diseases, including central nervous system demyelinating disease. Patients with chronic hepatitis B infection may develop the syndrome of chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids. Case presentation A 34-year-old Taiwanese man who had been a hepatitis B virus carrier for a decade presented to our emergency room. He had influenza symptoms and progressive symptoms of left hemifacial numbness, double vision, and an unsteady gait of 2 days' duration. Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids was diagnosed, with increased hepatitis B viral load at the same time. He had no past history of similar neurologic deficits, and his liver function tests had been within normal limits before this episode. After corticosteroid and entecavir treatments, his neurological deficits and neuroimaging anomalies improved and his serum hepatitis B virus DNA viral load normalized. Conclusions Hepatitis B virus infection may induce central nervous system autoimmune reactions, including chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids. In such cases, concomitant administration of corticosteroids and antiviral agent was helpful. We suggest further investigations in patients with regulatory T cell dysfunction, which may assist in clarifying a loss of immune tolerance in patients with such disorders.